PS02.239: SPECIFIC INHIBITION OF BONE MORPHOGENIC PROTEIN (BMP4) AS A POTENTIAL THERAPEUTIC STRATEGY FOR ESOPHAGEAL ADENOCARCINOMA. (14th September 2018) - Krishnadath, Kausilia; Hoefnagel, Sanne; Calpe, Silvia; Read, Matthew; Straub, Danielle; Correia, Ana; Sancho-Del Serra, Carmen
Abstract: Background: In Western countries, the highly malignant Esophageal adenocarcinoma (EAC) have the most dramatically rising incidence of all malignancies. BMP4 is a growth factor important for carcinogenesis. We found that BMP4 is aberrantly expressed in Barret's esophagus, the pecursor lesion of EAC, and that together with CDX2 drives the intestinalization of epithelial metaplasia. However, its role in esophageal adenocarcinoma (EAC) remains uncertain. Methods: Method: To elucidate whether BMP4 is involved in malignancy in EAC we used an RNA sequencing database of 56 EAC treatment naive endoscopic biopsies to investigate if there is a subgroup of cancers with high BMP signaling. We validated results by qPCR and immunohistochemistry in matching tumor samples. Next we used our recently developed effective and highly specific anti-BMP4 antibodies(1, 2) to study the effect of inhibition of BMP4 on both in vitro as well as in vivo models of EAC. Results: Using a gene set that was recently published for BMP signaling, we were able to distinguish a subgroup of EAC patients with increased BMP signaling. By IHC we confirmed that 70% of EAC tumors express BMP4 at the protein level. We found that patients with high levels of BMP4 expression tend to have a poorer recurrence-free survival compared to patients with low BMP4 expression, which suggests a more aggressive tumor behavior in BMP4 expressing EAC tumors. Most importantly, inhibition of BMP4 function in EAC cells by our recently developed anti-BMP4 antibodies lead to an increase in chemo-sensitivity and a decreased in invasive and migratory capabilities in vitro . Preclinical in vivo studies with a patient-derived tumor xenograft mouse model of an EAC tumor confirmed that anti-BMP4 antibodies can effectively reduce tumor growth and synergistically act with chemotherapy agents. Conclusion: We identified a subgroup of EAC with increased BMP signaling. Our studies support a role of BMP4 in chemo-resistance and invasiveness in EAC, and indicate that inhibition of BMP4 with highly our specific llama-derived antibodies is an attractive therapy for improving outcomes of EAC. Disclosure: All authors have declared no conflicts of interest.